The Concept of Legal Protection of Intellectual Property Rights of Traditional Jamu Communal Rights in Central Java - Zakariya, Hafid; ., Absori; Dimyati, Khudzaifah; Wardiono, Kelik (Journal of Ecohumanism, 2024)
This study aims to describe and provide empirical evidence regarding the legal protection of intellectual property rights for traditional herbal medicines based on communal rights in Central Java and to formulate the concept of legal protection for traditional herbal medicines based on communal rights. Theoretical Framework: This study uses the Theory of Legal Protection and the Theory of Defensive Protection to provide solutions to phenomena that occur in the field. It employs a purposive technique in sampling. The empirical concept is still known in legal research. Legal research views law in the scope of non-formal institutions and tries to understand legal behavior (the living law) in the context of social reality, legal protection of traditional herbal medicine, and also in the context of the reality of society that lives in groups and together. The findings of the study explain that Traditional Herbal Medicine Nguter, which is made and produced by the Nguter Local Community consisting of Herbal Medicine Business Actors, the Nguter Herbal Medicine Market, and also the Indonesian Herbal Medicine Cooperative, Kroya District, Cilacap Regency, Mijen District, Semarang City, and enjoyed by consumers in Nguter District, shows that traditional herbal medicine is a concoction that has been produced for generations and used by the Local Community. The existence of herbal medicine has its significance; however, it has not been optimally protected by the law by the State in the perspective of Intellectual Property Rights. The concept offered is legal protection for traditional herbal medicine as traditional knowledge by using the Defensive Protection concept, which is based on the fulfillment of communal rights. In this perspective, protection is achieved by publishing traditional herbal medicine openly, which can be accessed by Patent Examiners in Indonesia and abroad. The name of the publication is the Traditional Medicine Digital Library.